Congressional Hearings on Northern Ireland and the "Special Relationship, " 1971–1981. Issue 1 (2nd January 2016) - Sanders, Andrew
ABSTRACT: In 1971, Senator Edward Kennedy co-sponsored a resolution in Congress calling for the withdrawal of British troops from Northern Ireland. The House of Representatives Sub-Committee on Europe held hearings on this resolution in February 1972 in the immediate aftermath of the deaths in Londonderry of "Bloody Sunday." These hearings represented the first time that several high profile American political figures had spoken out on the developing conflict in Northern Ireland and, whilst the hearings did not lead to a significant change in American policy towards the conflict, the threat of further ones persisted from the Richard Nixon to the Ronald Reagan administrations. This analysis examines the impact of the 1972 Congressional hearings and the threat posed by the possibility of future ones in the wider context of United States policy towards the Northern Ireland conflict until 1981.